Magnetic and hydrophilic MWCNT/Fe composites as potential T2-weighted MRI contrast agents. (November 2015) - Maciejewska, Barbara M.; Warowicka, Alicja; Baranowska-Korczyc, Anna; Załęski, Karol; Zalewski, Tomasz; Kozioł, Krzysztof K.; Jurga, Stefan
Abstract: In this work, functionalized Multiwall Carbon Nanotubes of specified length and containing well-defined iron particles (O-MWCNT/Fe) were prepared. A significant enhancement in contrast in Magnetic Resonance Imaging was found for the investigated composites. The magnetic characterization revealed the ferromagnetic nature of iron particles embedded within O-MWCNTs. The enhancement of the 1 H spin–spin relaxation time of MRI scans using hydrophilic O-MWCNT/Fe as potential contrast agents was estimated for selected dispersive media. Moreover, the cytotoxicity of the hybrids was studied in two cell lines, i.e. cancer cells (HeLa) and fibroblasts (GM07492). The intracellular impact of O-MWCNT/Fes in HeLa cells was observed after staining of selected organelles (nuclei and mitochondria). Significant changes in cell morphology were found for water soluble MWCNT/Fes with diameters above 30 nm.